Proceso de atención de enfermería en paciente adulto mayor con hemorragia subaracnoidea. - Villamar Vizueta, Wilson Keiner (2023)
Subarachnoid hemorrhage is bleeding between the arachnoid mater and the pia mater. In general, head trauma is the most common cause of subarachnoid hemorrhage, but traumatic subarachnoid hemorrhage is often considered a separate entity. In the world the incidence of subarachnoid hemorrhage is constant and it is estimated that approximately 10 out of every 100,000 inhabitants/year suffer from this neurological pathology, in addition an estimate of close to 100 cases of subarachnoid hemorrhage per year in Ecuador has been provided. A nursing care process was applied to a female patient with a common symptomatic picture of the disease through the physical examination, its symptoms characterized by holocranial headache of spontaneous appearance, without irradiation, were also identified by means of the Marjory Gordon model. the altered patterns which allowed to identify the health needs of the patient. To carry out the diagnoses, interventions and results, the NANDA, NIC and NOC taxonomies were applied, which allowed to improve care and improve the quality of life of the patient during his hospital stay.